UJI RESISTENSI BAKTERI BASIL GRAM NEGATIF PADA SPUTUM PENDERITA PNEUMONIA TERHADAP ANTIBIOTIK LEVOFLOXACIN DAN CEFOTAXIM DI RSUP DR. SOERADJI TIRTONEGORO KLATEN - Ardy Prian Nirwana; Jatu Parmawati (LPPM Universitas Abdurrab, 2024)
Pneumonia is a common infection at all ages. It is the leading cause of death among all age groups with 4 million deaths (7% of the world's total mortality) (CDC, 2015). WHO in its 2017 report stated that more than 808,00 children under the age of 5 died from pneumonia. The purpose of this study was to determine the results of the sensitivity test of gram-negative bacilli bacteria in sputum samples of patients with pneumonia against Levofloxacin and Cefotaxime antibiotics at Dr. Soeradji Tirtonegoro Klaten General Hospital. This type of research is descriptive with purposive sampling technique. The population of this study were all sputum samples that were examined for culture at the Microbiology Laboratory of dr Soeradji Tirtonegoro Hospital. There were 26 samples with Acinetobacter baumannii as much as 32%, Klebsiella pneumoniae as much as 29%, Pseudomonas aeruginosa as much as 26%, Enterobacter cloacae as much as 10%, and Kluyvera ascorbata as much as 3%. Antibiotic resistance test against gram negative rod bacteria found 30% of bacteria resistant to levofloxacin antibiotics and 63% resistant to cefotaxime antibiotics.